THE EFFECT OF ULU AL-ALBAB-DRIVEN COMPETITIVE INTELLIGENCE (CI) ON THE ORGANISATIONAL PERFORMANCE OF THE INSTITUTIONS OF HIGHER LEARNING (HLIs) IN MALAYSIA: MODERATED BY ORGANISATIONAL FACTORS - Basri, Badrul Shahri; Mhd. Sarif , Suhaimi (Online Journal of Islamic Management and Finance (OJIMF), 2024)
An effective intelligence is necessary for profit and non-profit entities to formulating strategies and developing plans aim to sustain profitability, financially self-sufficient and competitive advantage. An effective intelligence is not just to acquire key input to the strategic planning for sustainable performance, but also to acquire strategic and accurate data before analysis. Competitive intelligence with ulu al-albab provides a comprehensive view that enhances professionalism by incorporating spirituality for al-falah. Institutions of higher education are crucial to society, particularly in creating skilled and high-quality graduates. Institutions of higher learning play an important to the society especially producing professional and quality graduates and also contributes to the development of the country. This study investigates the effect of competitive intelligence with ulu al-albab on the organisational performance of institutions of higher learning (IHLs) in Malaysia, moderated by organizational factors. The study embedded ulu al-albab, resource-based theory, and knowledge-based theory. 594 institutions of higher learning have been identified and 92 respondents participated in this study. The results suggested that there is a significant effect of ulu al-albab driven competitive intelligence on the organizational performance of IHLs in Malaysia even though without the support from organisational factors such as process and structure and awareness and culture. This study deepens and extends resource-based theory and knowledge-based theory driven by ulu al-albab in giving impact to the competitive intelligence on the organisational performance of institutions of higher learning in Malaysia.